Insect population distribution and density estimates in a large rice mill in Portugal – a pilot study - Carvalho, Maria Otília; Faro, Alexandra; Subramanyam, Bhadriraju (My University, 2013)
The objectives of this study were to characterize the spatial distribution of the most abundant insect species identified in the rice plant, optimize the sampling program, develop and validate a fixed-precision enumerative sequential sampling plan for the key pests Sitophilus spp. in a rice industry in Portugal. Experiments were carried out from September 2005 to July 2007, using 25 pitfall traps baited with food grade oil and pheromone specific for Sitophilus spp. The traps were observed weekly and the insects were identified and counted. Several species were found but Sitophilus zeamais Motschulsky and S. oryzae (L.) were the most abundant (90% of the total) followed by Tribolium castaneum (Herbst). Taylor’s power law parameters, from the regression of log variance versus log mean, suggest an aggregated distribution for Sitophilus spp. and T. castaneum. A fixed-precison sequential sampling plan was developed for Sitophilus spp., using Green’s fixed precisions sampling plan and the Resampling Validation of Sampling Plan, with an action threshold of 0.5 Sitophilus spp. The sampling plan was designed to provide precision levels of 0.20, 0.25 (for pest management purposes), 0.30 and 0.35. The current sample size raises a precision of 0.30, and an increase of the number of traps to 37 would be recommendable to fit the desirable precision of 0.25. This fixed-precison sequential sampling plan for Sitophilus spp. populations in rice demonstrated to be useful as a tool in IPM tactics at rice facilities.
Keywords: Stored rice; Sitophilus spp.; Tribolium castaneum; Floor traps; Fixed precision sampling plan; Distribution pattern; Taylor's power law